2021
DOI: 10.3389/fendo.2021.681148
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Childhood Thyroid Cancer incidence in Korea and Its Potential Risk Factors

Abstract: BackgroundAlthough the incidence of thyroid cancer had been increasing until a few years ago, a decrease has been observed in the last years, probably due to the reduction of the screening tests in Korea. Childhood thyroid cancer has been increasing in the past with the same trend as in adults, but there have been few reports on recent trends. We analyzed the trends of thyroid cancer in Korean children and related factors.MethodsFrom national statistics and cancer register database, the data of age-specific in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…After that, the IR tended to de-crease; however, this decrease was insignificant. In patients in their 30s, the IR increased from 28 1, 2, Fig. 2D).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…After that, the IR tended to de-crease; however, this decrease was insignificant. In patients in their 30s, the IR increased from 28 1, 2, Fig. 2D).…”
Section: Resultsmentioning
confidence: 87%
“…Additionally, some recent studies reported the increasing incidence of childhood thyroid cancer in Korea [28,29] and worldwide [30][31][32]. In Korea, thyroid cancer is the most common cancer in both sexes among the adolescent and young adult populations (15 to 34 years), accounting for 50.8% of all cancers [17].…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…East Asia, including Korea, Japan, and China, is characterized by high iodine intake, primarily from seafood consumption, especially seaweed [16,17]. Recent cohort studies have suggested a potential link between seaweed consumption and a reduced risk of cardiovascular diseases, possibly through blood pressure-and lipid-lowering effects [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that obesity is a risk factor for thyroid cancer [ 5 , 6 ]. In a meta-analysis, the risk of thyroid cancer increased in a dose-dependent manner with increasing body mass index [ 7 ].…”
Section: Introductionmentioning
confidence: 99%